PERBANDINGAN PENYESUIAN DIRI NARAPIDANA DENGAN STRATEGI COPING DI LAPAS NARKOTIKA KELAS IIA GUNUNG SINDUR - Adhitya Putra Yuntoro; Mitro Subroto (NUSANTARA : Jurnal Ilmu Pengetahuan Sosial, 2022)
In this modern era, people in general already know what drugs are. Narkoba stands for narcotics, psychotropic substances and other dangerous addictive substances. According to article 1 paragraph (1) of Law No. 35 of 2009 concerning Narcotics defines narcotics as a substance or drug whose ingredients come from plants or non-plants, either synthetic or systematic, which can cause a decrease or change in consciousness, loss of pain. , minimize to eliminate pain and can cause dependence. The approach used in this research is a quantitative approach. The quantitative approach is a process of finding knowledge by using data in the form of numbers as a tool to analyze information about what you want to know. This study uses a comparative quantitative method. Comparative research is research conducted to compare a variable (object of research) between different subjects or at different times and find causal relationships. Individuals in the face of a new environment will give an assessment of the situation they are experiencing and then assess whether the situation is relevant to their welfare or on the contrary will be a threat to their welfare. Inmates are emotionally increased due to the transition and adjustment to their new environment. Based on the hypothesis test or difference test, the data shows the average adjustment of the Coping Strategy group is 54.34 and the average adjustment of the Self-adjustment group is 53.97. This shows that there are differences in adjustment between prisoners and coping strategies in Gunung Sindur Class IIA Narcotics Penitentiary.